2015
DOI: 10.3390/ma8115391
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution at Micro/Meso-Scale in an Ultrafine-Grained Pure Aluminum Processed by Equal-Channel Angular Pressing with Subsequent Annealing Treatment

Abstract: Micro-forming with ultrafine-grained (UFG) materials is a promising direction for the fabrication of micro-electro-mechanical systems (MEMS) components due to the improved formability, good surface quality, and excellent mechanical properties it provides. In this paper, micro-compression tests were performed using UFG pure aluminum processed by equal-channel angular pressing (ECAP) with subsequent annealing treatment. Microstructural evolution was investigated by electron back-scattered diffraction (EBSD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Saotome et al investigated the effect of grain size on filling behavior during embossing process and found that the finer grain provided better filling ability. Similar phenomenon was also proved to be valid for the pure Al, pure Cu, pure Ni, and magnesium alloy . Thus, it was confirmed that grain size effect would influence the forming behavior during micro‐embossing and UFG‐grained materials were of better formability.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Saotome et al investigated the effect of grain size on filling behavior during embossing process and found that the finer grain provided better filling ability. Similar phenomenon was also proved to be valid for the pure Al, pure Cu, pure Ni, and magnesium alloy . Thus, it was confirmed that grain size effect would influence the forming behavior during micro‐embossing and UFG‐grained materials were of better formability.…”
Section: Introductionsupporting
confidence: 69%
“…High purity (99.999%) aluminum was applied as an initial material. The equal‐channel angular pressing (ECAP) for pure Al was carried out at room temperature and the corresponding process parameters were provided by the previous research . After 8 ECAP passes, UFG pure Al with an average grain size of approximately 1 μm was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The methods of severe plastic deformation (SPD) are an effective means of grain refinement [1][2][3][4], which have been widely used in the preparation of ultra-high strength materials. The SPD methods mainly include cold rolling [5,6], equal channel angular pressing (ECAP) [7][8][9], high-pressure torsion (HPT) straining [10,11], accumulative roll-bonding (ARB) [12][13][14], multidirectional forging (MDF) [15][16][17], etc. Valiev et al [18,19] reported the preparation and application of bulk nanostructured materials from SDP.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there is an obvious transition from nonuniform deformation to uniform deformation after micro-compression testing with decreasing of grain size as shown in Figure 8a-e. The nonuniform deformation can be improved significantly, and the compressed specimens using UFG pure Al are cylindrical with a smooth surface as shown in Figure 8d and e [77,78]. Research on the micro-extrusion of UFG aluminum showed that the material flow became more uniform because more grains were deformed during micro-extrusion [79].…”
Section: Potential Application In Micro-forming Technologymentioning
confidence: 99%